Corrosion inhibition of steel in 3.5 NaCl by rice straw extract - Othman, N.K. (2019)
Inhibition of steel corrosion in 3.5 sodium chloride (NaCl) by rice straw extract (RSE) was studied via weight loss method up to 42 days immersion. The corrosion inhibition efficiency (IE) showed a consistent value with the highest IE of 92 and low corrosion rate, 0.013 mm/y. RSE was able to reduce pitting corrosion by presenting small hysteresis loop via cyclic polarization measurement. The formation of ferric-RSE layer due to complexation was confirmed via surface analysis. The presence of corrosion products on steel was significantly reduced by immersion in RSE. The inhibitory mechanism was proposed to be achieved through interphase inhibition. Â© 2018 The Korean Society of Industrial and Engineering Chemistry